A Comparative X-ray Investigation for the AnodeComponent in Thermal Batteries - H. HUSSEIN, FALAH; N. ALKHATEEB, AHMED; D. OMRAN, KAREEM; M. SARHAN, WALEED (Asian Journal of Chemistry, 2010)
In this investigation, a comparative X-ray study for the anode of the foreign thermal cell and that of the assembled one have been carried out. The results have been compared with those issued by the American Society for Testing Materials (ASTM). A comparative investigation for the X-ray diffraction of the anode component of the foreign cell as well as the linear spectrum for the diffraction of this component revealed that this anode is a Ca electrode. The evidence came from the formation of Ca(OH)2 accompanied by the liberation of H2, as a result of the action of moisture on Ca. Six peaks of different intensities for Ca(OH)2 were observed. A comparison for The X-ray diffraction values and the linear spectrum at 400°C, for the anode component of the assembled cell, has been carried out. After running the cell, the findings displayed that the electrode contained the compounds KCl, CaO, Li2CrO4, CaCrO4, Ca(OH)2 and CaCl2, explaining the increment of the operation time for the cell, with a low voltage. The incomplete solubility of CaCrO4 at 400°C gave rise to the slowdown of the thermochemical reactions, leading ultimately to the ascent of the operation period. A similar comparison was accomplished at 460°C; which is the temperature at which the cell was operating with maximum efficiency, to confirm that the anode mixture induded Ca(OH)2, CaO and LiCrO2. Finally, a comparative study of the X-ray diffraction for the anode of the assembled thermal cell at 600°C, that was the temperature at which the complete consumption of the cell took place, disclosed throughout the amplitude d-values, that this electrode contained CaO, Ca(OH)2 and the oxide mixture LiO2·Cr2O3. No change occurred upon the development of the compounds on the anode.